Inducible general knockout of Runx3 profoundly reduces pulmonary cytotoxic CD8+ T cells with minimal effect on outcomes in mice following influenza infection - Hao, Qin; Kundu, Suman; Shetty, Sreerama; Tucker, Torry A.; Idell, Steven; Tang, Hua (Frontiers in Immunology, 2022)
Respiratory viruses pose a continuing and substantive threat to human health globally. Host innate and adaptive immune responses are the critical antiviral defense mechanisms to control viral replication and spread. The present study is designed to determine the role of transcription factor Runx3 in the host immune response to influenza A virus (IAV) infection. As Runx3 is required for embryonic development, we generated an inducible Runx3 global knockout (KO) mouse model and found that Runx3 KO in adult C57BL/6 mice minimally affected thymic function under normal conditions and survival was at least 250 days post Runx3 deletion. We applied the mouse model to IAV infection and found that Runx3 KO resulted in a huge reduction (>85%) in numbers of total and antigen-specific pulmonary CD8+ cytotoxic T cells during IAV infection, while it had a minor effect on pulmonary generation of CD4+ T cells. To our surprise, this general KO of Runx3 did not significantly alter viral clearance and animal survival following IAV infection. Interestingly, we found that Runx3 KO significantly increased the numbers of pulmonary innate immune cells such as macrophages and neutrophils and the production of pro-inflammatory cytokines during IAV infection. We further found that Runx3 was strongly detected in CCR2+ immune cells in IAV-infected mouse lungs and was induced in activated macrophages and dendritic cells (DCs). As pulmonary CD8+ cytotoxic T cells play a central role in the clearance of IAV, our findings suggest that Runx3 KO may enhance host innate immunity to compensate for the loss of pulmonary CD8+ cytotoxic T cells during IAV infection.